ASSESSMENT OF HEAVY METAL SOIL CONTAMINATION IN SOME NORTHEASTERN ALGERIAN BIOTOPES BY USING THE TERRESTRIAL SNAIL, HELIX ASPERSA - Guessasma, Z; Khaldi, F; Grara, N; Agouni, M; Sleimi, N.; Benslama MOHAMED (My University, 2020)
The study was aimed to assess the ecotoxicological impact of anthropogenic activities on soil quality by using the land snail Helix aspersa as a bioindicator. Soil samples and snails were collected from several sites of northeast Algeria during spring and winter, 2017. All sites were chosen in this study for the reason of their proximity to industrial factories as a potential source of heavy metal soil contamination. The concentration of heavy metals in soil samples was analyzed using the X-ray Fluorescence (XRF) spectrometer (Thermo Scientific Model Niton FXL 950) since the three metals of the highest levels in soil samples were examined in Helix aspersa hepatopancreas and feet by means of the atomic absorption spectrophotometry. Also, the highest levels of heavy metals were noticed during spring in Helix aspersa of the closest sites to the potential sources of pollution. These results are correlated with the physico-chemical characteristics of soil (texture, organic matter, pH Water, conductivity, limestone, and porosity) in each site